Multimodality and Racial Representation Suggested in E foi assim que eu e a escuridão ficamos amigas, by the Rapper Emicida (Revista de Estudos da Linguagem, 2024)
It is known that multimodality is an inherent characteristic in any text, however, in areas such as literature, it still faces obstacles to being fully recognized as a carrier of meaning and as an object of aesthetic appreciation, partly because of the culture of praise of the written verbal text that lasted for much of the history of literary studies. However, new perspectives brought to light by the propagation of texts that mix different semiotic modes, especially those published in digital media, have indicated that the literary text begins to be seen with different eyes. The same can be said in relation to the adoption of a perspective for reading the literary text as a tool for social awareness, empowerment and action aimed at solving problems, such as racism and social inequalities linked to ethnicity. From these perspectives, in this text, we present a multimodal analysis of the children’s work E foi assim que eu e a escuridão ficamos amigas, both in its printed and in its audiovisual version, to demonstrate that although the verbal utterances do not explicitly present connotations linked to the appreciation of black culture, such meanings are expressed through the multimodal relationship established between written, sound and visual verbal texts, among others. At the end of the analysis, we suggest transmodality (Bezermer; Kress, 2008), as a theoretical framework suitable for the interpretation of the referred texts.